PENGARUH PEMERIKSAAN PAJAK TERHADAP TINGKAT KEPATUHAN PEMENUHAN KEWAJIBAN PERPAJAKAN FORMAL OLEH WAJIB PAJAK BADAN (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA SAMARINDA) - Saputro, Hendro (EKONOMIA, 2012)
The tax system adopted by our country is a self-assessment system, in which the taxpayer is given full trust to count, calculate, deposit, and report the tax itself, however, in the early stages of the implementation of this system is that not all taxpayers will obey tax obligations and more likely to minimize the tax burden should be payable and slow in paying taxes. Thus, it needs a method of testing the truth in order to secure the fulfillment of tax obligations of state income taxation sector. This has subsequently become one of the Directorate General of Taxation to conduct Tax Audit. Tax Audit aims to test compliance with tax obligations fulfillment and / or for other purposes in order to implement the provisions of the tax laws so that the examination is expected to increase taxpayer compliance. Based on the analysis it can be concluded that the tax had a significant effect on the fulfillment of formal compliance increased taxation by the taxpayer loss in Pratama Samarinda Tax Office during 2009 to 2011